RESPON INDONESIA TERHADAP PRODUK MAKANAN CHINA YANG MENGANDUNG ZAT BERBAHAYA (FORMALIN) TAHUN 2007 - Fatmala, Shinta; Waluyo, Tri Joko (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research used qualitative research methods that the source data is takenfrom books, journals, media, internet, and previous research has relevant datawith the title. Perspectives and levels of analysis used in this study is that the stateas the main actor. This research also using the concept of national interest andthe theory of trade disputes. This research will explain the Indonesian responseabout this case. Diplomatic relation between Indonesia and China has beenestablished since 1990 and it runs very well. Problem appeared in 2007 whenChina’s food product contained hazardous substances (formaldehida) andunstandardization indicated spreaded and distributed widely in Indonesia. Theresults of this research showed that Indonesia governm launched a publicwarning number KH. 01.84.53.094 about China’s food product containedhazardous substances (formaldehida), appeal for not consume China’s foodproduct in the list of that public warning and conduct meeting with China’sgovernment to discuss about the food standardizations and healthy food quality.Key Words : Formaldehida Public Warning Food standardization